A WD40-repeat protein from persimmon interacts with the regulators of proanthocyanidin biosynthesis DkMYB2 and DkMYB4 - Naval, María M.; Gil-Muñoz, Francisco; Lloret, Alba; Besada, Cristina; Salvador, Alejandra; Badenes, María L.; Ríos, Gabino (Springer, 2020)
MYB-bHLH-WD40 (MBW) ternary complexes composed of MYB domain proteins, basic helix-loop-helix (bHLH) transcription factors and WD40-repeat proteins are involved in the transcriptional regulation of anthocyanin and proanthocyanidin (PA) biosynthesis pathways in distinct plant species. PAs are the compounds responsible for the strong astringent taste of persimmon fruit. DkMYB2 and DkMYB4 (MYB type) and DkMYC1 (bHLH type) genes from persimmon have been postulated to regulate the biosynthesis of PAs in fruit.We have identified a WD40-repeat gene from persimmon (DkWDR1) coding for a protein highly similar to TTG1 from Arabidopsis thaliana and other WD40-repeat components of distinct MBW complexes. DkWDR1 expression was detected in different tissues and was essentially constant during fruit development. MYB-like proteins DkMYB2 and DkMYB4 interacted with both DkWDR1 and DkMYC1 in the yeast two-hybrid system. The sequence of DkWDR1 and the analysis of yeast two-hybrid interactions with known regulators of PA biosynthesis support the occurrence of MYBbHLH-WD40 (MBW) complexes in persimmon, to regulate PA accumulation in fruit.